Prove that (AB)^-1 = B^-1 A^-1

This problem can be solved in 8 steps:

1. Let AB = C

2. A-1AB = A-1C

3. IB = A-1C as the identity matrix I = A-1A

4. B-1B = B-1A-1C premultiply both sides by B-1

5. I = B-1A-1C as B-1B = I, the identity matrix

6. C-1=B-1A-1CC-1 post multiple both sides by C-1

7. C-1=B-1A-1 as CC-1 = I, the identity matrix

8. (AB)-1=B-1A-1

Related Further Mathematics A Level answers

All answers ▸

Are we able to represent linear matrix transformations with complex numbers?


Simplify (2x^3+8x^2+17x+18)/(x+2)


solve the 1st order differential equation 2y+(x*dy/dx)=x^3


Prove that "6^n + 9" is divisible by 5 for all natural numbers.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences